HUBUNGAN BEBAN KERJA DENGAN TINGKAT STRES PERAWAT - Putri Ladia; Meynur Rohmah; Zahrah Maulidia Septimar (Nusantara Hasana Journal, 2021)
In the United States about 11 million people suffer from work stress. Another survey shows that nearly a quarter of Americans consider work stress to be the biggest and most important problem in life. Method: Literature study This writer uses traditional literature studies with reseach studies and systematic approaches namely thematic analysis, simplified approach. In searching for several articles, this literature uses the PICO strategy with inclusion criteria, namely using two languages, namely Indonesian and English, respondents are nurses who work in hospitals, articles that are obtained from primary sources and are vulnerable when the article is 5 years (2015-2020 ). Results: Based on the Literature study, there was a correlation between workload and nurses work stress. Thus, nurses who experience excessive workload will be vulnerable to increased work stress.